Avaliação dos impactos da mudança na metodologia de cálculo da taxa de juros do FNE - Oliveira, Cristina Chaves de (2021)
Constitutional financing funds are one of the main instruments of the National Policy for Regional Development (PNDR) in combating regional inequalities and fostering regional development. Since its creation, the rule for calculating financial charges for constitutional funds has undergone several changes. The most recent, resulting from Law No. 13,682, of June 19, 2018, associated the financial charges for the operations of these funds with the fixed interest rate of the TLP and the IPCA, no longer being fixed by the National Monetary Council. In this context, considering the importance that these resources represent in the economies of the regions to which they are destined, the present study sought to analyze the dynamics in the volume of applications, specifically of the FNE, in the period of 2010-2019, verifying mainly the impacts resulting from this change. For this, the structural instability test for breaks at the end of the sample was adopted, proposed by Andrews (2003), due to the difficulty associated with the short time available for the post-change of methodology period in the calculation of interest associated with the credit from FNE, which took place in January 2018. In addition to the variable of interest, which reflects the volume of credit operations contracted with FNE resources, the control variables of the Central Bank's Regional Economic Activity Index and the Balance of Operations were used of Credit carried out by financial institutions, in order to reflect the state of the economy and the degree of competitiveness in credit operations, both in regional terms. The results obtained suggest that the change in methodology in the interest rate caused a positive impact on the volume of operations carried out with FNE resources, confirming the hypothesis that the new methodology improved the systematic remuneration system for constitutional funds, enabling rates that are more in line with those of the FNE. needs of the final borrower of resources from constitutional funds, expanding the demand for FNE resources.